The determinants of social self‐efficacy of tourism lifestyle entrepreneurs - Sousa, L.; Dias, Á.; Pereira, L. (International Journal of Tourism Research, 2023)
Tourism Lifestyle Entrepreneurs (TLEs) play a vital role in destination competitiveness by providing creative and co-created experiences intrinsically associated with local communities. To preserve their way of life, they are also deeply involved in local social activities. However, the processes underlying the social performance of these entrepreneurs remain underexplored. This study uses structural equations modelling to analyse the influence of TLE’s social dimensions (community attachment, social mission orientation, and community-centred strategies) on social self-efficacy. Results reveal that social mission, community-centred strategy, and community attachment have a significant positive influence on social entrepreneurial self-efficacy through the indirect effect of co-creation. Findings also highlight the mediating role of co-creation in those relationships, indicating the importance of providing unique and memorable experiences to fulfil their social goals.